Pengaruh Nilai Kepuasaan Faktor Suplai terhadap Loyalitas Pengunjung Pada Objek Wisata Posong - Zukruf Novandaya; Holi Bina Wijaya (Teknik PWK (Perencanaan Wilayah Kota), 2021)
The dominant visitor satisfaction factor is influenced by tourism supply factors (attractions, accessibility, amenities, and ancilliery services) provided by the tour manager. The development and sustainability of tourism activities will have an impact on people's income can be seen from the value of visitor loyalty. Tourism that utilizes local resources will have an impact on the local economy of the region. Posong Tourism as a tour that utilizes local resources, namely the mountain view initiated by the community. The supply factor at Posong Tourism was also initiated and provided by the local community. The purpose of this study was to assess the effect of visitor satisfaction from supply factors on tourist visitor loyalty in the Posong Tourism object, Temanggung Regency. The research method used is a quantitative research method using Structural Equation Modeling Analysis (SEM). The results showed a significant direct effect between the supply of Posong Tourism supply factors to the value of visitor satisfaction, and there was also the influence of visitor satisfaction on the value of loyalty. In addition, the results of the analysis of theoretical models there are 9 indicators that have an indirect influence.